Explaining the distribution of manufacturing productivity in the EU regions - Enrique Lopez-Bazo; Bernard Fingleton (European Regional Science Association (ERSA), 2003)
Regional inequalities in product per capita and labour productivity in the EU are large and persistent. Building on a model in which aggregate increasing returns is the result of the increase in the number of varieties of composite services, under competitive manufactures, we derive a simple and empirically tractable reduced form linking manufacturing productivity growth to the growth of manufacturing output. This specification is used to simulate the equilibrium distribution of labour productivity in the EU regions, that is compared with "virtual" distributions obtained by equalizing, for instance, the amount of returns to scale and the stock of human capital across regions. This way, the impact of some growth determinants on the whole EU regional equilibrium distribution can be assessed.
Keywords: 330